2011
DOI: 10.1016/j.neulet.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure increases levels of β-amyloid in the brain and CSF and inhibits LRP1 expression in APP transgenic mice

Abstract: Lead (Pb) is an environmental factor suspected of contributing to neurodegenerative diseases such as Alzheimer’s disease (AD). In AD, it has been postulated that increased production and/or decreased metabolism/clearance of beta-amyloid (Aβ) may lead to amyloid plaque deposition as well as a cascade of other neuropathological changes. It has been suggested that Pb exposure may be associated with AD-like pathology and severe memory deficits in humans. Therefore, we investigated whether Pb exposure could induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 31 publications
5
39
0
Order By: Relevance
“…U.S. Department of Health and Human Services and Environmental Protection Agency (EPA) have listed Pb compounds to be carcinogens, neurotoxicant, and neurodevelopmental toxicant (UNEP, 2006; IARC, 2006). Recent epidemiologic studies have also linked Pb exposure to the declined cognition (Bakulski et al, 2012) and the etiology of Alzheimer’s disease (Gu et al, 2011, 2012; Schwartz et al 2010; Stewart et al, 2006). Main sources of Pb exposure in the general population are food, water and airborne particulate (smoke included) (Forte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…U.S. Department of Health and Human Services and Environmental Protection Agency (EPA) have listed Pb compounds to be carcinogens, neurotoxicant, and neurodevelopmental toxicant (UNEP, 2006; IARC, 2006). Recent epidemiologic studies have also linked Pb exposure to the declined cognition (Bakulski et al, 2012) and the etiology of Alzheimer’s disease (Gu et al, 2011, 2012; Schwartz et al 2010; Stewart et al, 2006). Main sources of Pb exposure in the general population are food, water and airborne particulate (smoke included) (Forte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An amyloid precursor protein (AβPP) transgenic mouse model overexpressing human AβPP with a mutation (V717F) that causes an autosomal dominant form of familial AD was utilized (Gu et al, 2011). In this study, 3 month old mice showed high levels of human Aβ protein in brains without having plaques, which was consistent to previous reports demonstrating these mice had an age-related accumulation of Aβ plaques in brains starting from 6 months of age (Bales et al, 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Since the CP is in direct continuity with the cerebral interstitial fluid (ISF) and the CSF, Aβ in the brains extracellular space can freely enter into the CSF. Immunoreactive Aβ and its precursor protein AβPP in the CP (Sasaki et al, 1997, Crossgrove et al, 2007) suggests that the CP may be involved in the brains Aβ clearance (Crossgrove et al, 2005, Behl et al, 2009a, Gu et al, 2011). Thus, it is interesting to explore the role of the BCB in the brain Aβ clearance and IVIG-induced efflux of Aβ from brains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the expression of many transporters/receptors and IDE on the choroid plexus and the ependymal cells has been reported, as presented in Table 1. Furthermore, the contributions of LRP1 (Behl Fujiyoshi et al 2011;Gu et al 2011), LRP2 (Zlokovic et al 1996Carro et al 2005) and IDE (Behl et al 2009) to Aβ clearance in the choroid plexus have been demonstrated. The expression of LRP1 was increased in the CP of aged rats and AD mice; that of LRP2 was decreased in the CP of aged humans, aged rodents and AD mice; and that of ABCB1 (P-gp) was increased in the CP of aged rats, implying the enhancement and/or compensatory effect on Aβ clearance from CSF at the BCSFB with aging and amyloid burden (Carro et al 2005;Johanson et al 2006;Dietrich et al 2008;Pascale et al 2011;González-Marrero et al 2015).…”
Section: Introductionmentioning
confidence: 96%